THEORETICAL SUBSTANTIATION OF THE UNIFORMITY OF THE DEPTH OF THE RIPPER STROKE OF THE MACHINE FOR PRE-SOWING TREATMENT OF RIDGES (Conference Zone, 2022)
The article presents the results of research on the justification of the angle of inclination to the horizon of the longitudinal links of the mechanism for mounting the ripper of the machine for pre-sowing treatment of ridges in order to ensure uniform loosening of their tops.